2017
DOI: 10.1038/ijo.2017.139
|View full text |Cite
|
Sign up to set email alerts
|

Long-term health outcomes in patients with Prader–Willi Syndrome: a nationwide cohort study in Denmark

Abstract: Multiple cardiovascular and behavioral illnesses are more likely to occur among patients with PWS than within the general population. These increased risks may provide an impetus for enhanced disease prevention, screening, diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 49 publications
0
39
0
1
Order By: Relevance
“…Intellectual disability, growth hormone deficiency, behavioral problems, including aggressive and threatening behaviors, and neuroendocrine abnormalities are also characteristic of PWS [88]. The death rate among PWS patients is markedly elevated [90]. According to a 2014 survey of parents and caregivers of PWS patients, reducing hunger and improving food-related behaviors were the most important unmet needs in PWS that could be addressed in the development of a new therapeutic [91].…”
Section: Experience With the Diazoxide Choline Controlled-release Tabmentioning
confidence: 99%
“…Intellectual disability, growth hormone deficiency, behavioral problems, including aggressive and threatening behaviors, and neuroendocrine abnormalities are also characteristic of PWS [88]. The death rate among PWS patients is markedly elevated [90]. According to a 2014 survey of parents and caregivers of PWS patients, reducing hunger and improving food-related behaviors were the most important unmet needs in PWS that could be addressed in the development of a new therapeutic [91].…”
Section: Experience With the Diazoxide Choline Controlled-release Tabmentioning
confidence: 99%
“…Without strictly supervised caloric restriction and regular exercise, appetite disturbances and physical difficulties predispose the majority of children to child‐onset obesity. The Danish National Patient Registry database reported that individuals with PWS ( n = 155) were 10 times more likely to be obese and 9 times more likely to be diagnosed with type 2 diabetes mellitus than the matched general population ( n = 15 500) . The development of obesity and impaired glucose metabolism are linked to various aspects of hypothalamic pituitary axis dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…Abnormalities in hormones influencing appetite regulation and satiety signalling, such as ghrelin or peptide YY, may contribute to the hyperphagia in PWS . Obesity contributes to the increased risk of obstructive sleep apnoea, cardiovascular disease, reduced bone mineral density and fracture and scoliosis observed in patients with PWS …”
Section: Resultsmentioning
confidence: 99%
“…Genes 2020, 11, 67 2 of 11 between obesity and early death in adults with PWS [4]. Comorbidities that are commonly associated with obesity in PWS include respiratory problems (pulmonary embolism, respiratory failure, and pulmonary hypertension) and deep venous thrombosis [5][6][7][8][9].…”
Section: Have Suggested An Important Associationmentioning
confidence: 99%
“…An increased risk of venous thromboembolisms (VTEs) was recently reported in PWS patients by using Prader-Willi syndrome Association (USA) syndrome-specific database of deaths between 1973 and 2015 [5,9]. Seven percent of all deaths in the reported PWS survey commonly found in adulthood were attributable to pulmonary embolism, which represented only a quarter of the most common causes of death that were related to respiratory failure [5,6].…”
Section: Have Suggested An Important Associationmentioning
confidence: 99%